Observation of shock-induced protein crystal damage during megahertz serial femtosecond crystallography - Marie L. Grünbein; Lutz Foucar; Alexander Gorel; Mario Hilpert; Marco Kloos; Karol Nass; Gabriela Nass Kovacs; Christopher M. Roome; Robert L. Shoeman; Miriam Stricker; Sergio Carbajo; William Colocho; et al. (Physical Review Research, 2021)
Shock waves launched by x-ray pulses in sample-carrying liquid jets may affect protein crystallography data collected at MHz repetition rate x-ray free-electron laser (XFEL) facilities, by damaging the crystals before they are probed. We investigated the shock damage in lysozyme microcrystals using a double-pulse operation mode at a low repetition rate x-ray laser facility. The double-pulse mode generated shock waves with pressures that covered and exceeded the shock pressures expected at MHz pulse rate experiments at the European XFEL (EuXFEL) x-ray laser. The quality of the x-ray diffraction data from the crystals was degraded after the shock passed. A decrease in the number of peaks and in the resolution occurred above an estimated shock pressure threshold on the order of tens of MPa. Based on the scaling of the shock pressure with the sample injection parameters and the pulse rates, this threshold was not reached in initial EuXFEL experiments performed at pulse rates of 1.1 MHz but may be exceeded at the maximum pulse rate of 4.5 MHz. The observation of shock damage in lysozyme crystals indicates how experiments can be designed to rapidly detect, and eventually avoid, shock damage in other crystals. Our analysis of shock pressures in liquid jets can also be used to estimate the effect of the shocks in other types of experiments at MHz repetition rate XFELs.